Pengaruh Literasi Digital, Online Resilience dan Peran Orang Tua Terhadap Pencegahan Cyberbullying Pada Remaja SMAN 1 Cijaku di Kabupaten Lebak Tahun 2025 - Abela Mayunita; Maemunah Maemunah (Jurnal Ners, 2025)
Teenagers who previously only knew the physical and social world directly are now connected to a virtual world full of opportunities and challenges. However, along with the benefits offered by digital technology, various problems also arise that can affect children's psychological and social development, one of which is cyberbullying. In Indonesia, the phenomenon of cyberbullying is increasing, along with the high level of internet use by teenagers. Based on data from the United Nations International Children Educational Fund (UNICEF), as many as 45 percent of teenagers in Indonesia aged 14-24 years have experienced cyberbullying or online bullying. In the context of preventing cyberbullying, digital literacy is very important so that teenagers can recognize potential threats in cyberspace and know how to deal with them. Apart from digital literacy, online resilience and the role of parents also play an important role in reducing the impact of cyberbullying. This research aims to find out whether there is an influence of digital literacy, online resilience and the role of parents on preventing cyberbullying in teenagers at SMAN Cijaku in Cijaku in 2025. This type of research is analytical descriptive research with hypothesis testing using a cross sectional approach. Data collection was carried out from November 2024 to January 2025. The sampling technique was random sampling, namely randomly from students who had social media at SMAN I Cijaku. Data collection uses a questionnaire instrument. There is an influence of digital literacy with a significance value of 0.001 (<0.05), there is an influence of online resilience with a significance value of 0.001 (<0.05) and there is an influence of the role of parents with a significance value of 0.001 (<0.05) on preventing cyberbullying in adolescents. Cijaku High School in Cijaku in 2025.